Relationship of Dietary Intake of Omega-3 and Omega-6 Fatty Acids with Risk of Prostate Cancer Development: A Meta-Analysis of Prospective Studies and Review of Literature. (5th November 2012) - Chua, Michael E.; Sio, Maria Christina D.; Sorongon, Mishell C.; Dy, Jun S.
Abstract : Objective . To determine the relationship between dietary omega-3 fatty acids ( n -3 PUFA) and omega-6 fatty acids ( n -6 PUFA) with prostate cancer risk from meta-analysis of prospective studies. Design . The literature retrieved from electronic biomedical databases up to June 2011 was critically appraised. General variance-based method was used to pool the effect estimates at 95% confidence interval. Heterogeneity was assessed by Chi 2 and quantified by I 2 . Results . Eight cohort studies were included for meta-analysis. n -3 PUFA, n -6 PUFA, and their derivatives were not significantly associated with risk of prostate cancer in general. A significant negative association between high dietary intake of alpha-linolenic acid (ALA) and prostate cancer risk (pooled RR: 0.915; 95% CI: 0.849, 0.985; P = 0.019 ) was noted. Likewise, a slightly positive association was noted on dietary long-chain n -3 PUFA, composed of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) with prostate cancer risk (pooled RR: 1.135; 95% CI: 1.008, 1.278; P = 0.036 ); however, when two other cohort studies with data of EPA and DHA, both analyzed separately, were included into the pool, the association became not significant (RR: 1.034; 95% CI: 0.973, 1.096; P = 0.2780 ). Conclusion . Intake of n -3 PUFA and n -6 PUFA does not significantly affect risk of prostate cancer. High intake of ALA may reduce risk of prostate cancer, while intake of long-chain omega-3 fatty acids does not have a significant effect.